Peculiarities of the general and social intelligence of students of different chiefs - D M Andrianov (Peoples' Friendship University of Russia (RUDN University), 2009)
The results of empirical research of features of general and social intelligence of students and the connection of these two concepts are presented in the article. The basic powers of thought influencing development of social intelligence are revealed.